A novel process of salt tolerance partial denitrification and anammox (ST-PDA) for treating saline wastewater. (February 2022) - Xu, Ao; Yu, Deshuang; Qiu, Yanling; Chen, Guanghui; Tian, Yuan; Wang, Yanyan
Graphical abstract: Highlights: ST-PDA process was established for dealing with saline wastewater. Stable nitrogen removal of PD and Anammox was achieved under 10 g·L -1 salinity. Inhibition of NO3 – -N and FNA was verified and FNA inhibition could be eliminated with self-alkalization. The TN of effluent from ST-PDA process was average 17.8 mg·L -1 . Thauera showed a high tolerance to fluctuating salinity levels. Abstract: In the study, the salt-tolerant partial denitrification and Anammox (ST-PDA) process was established, meanwhile, the feasibility of salinity inhibition model as the boundary control method and the subsequent operation performance were studied. Study indicated that the performance of salt-tolerant PD sludge was the optimum under the 10 g·L -1 salinity, and AnAOB also maintained high activity at the salinity. Haldane and Aiba models verified that NO3 – -N (substrate) and FNA (product) would have negative consequences for performance of ST-PDA system. However, the effect of FNA would be eliminated by self-alkalization in the denitrification process. A 90% nitrogen removal rate was achieved and the average effluent total nitrogen of 17.8 mg·L -1 was maintained in the system. The high throughput sequencing revealed that the species richness decreased with the salinity increased, while Thauera played a major role in nitrogen removal in saline environment. The study provides a novel insights for salt-containing industrial wastewater.